2016
DOI: 10.21037/jtd.2016.12.44
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of red cell distribution width in elderly patients undergoing resection for non-small cell lung cancer

Abstract: Background:The impact of red cell distribution width (RDW) on outcomes in elderly patients after surgery for non-small cell lung cancer (NSCLC) is not fully understood. Methods: We retrospectively analyzed 992 NSCLC patients who underwent curative resection between 1998 and 2012. The following variables were included in the analyses to evaluate the role of RDW: age, gender, smoking index, leukocyte count, neutrophil to lymphocyte ratio (NLR), hemoglobin, platelet count, albumin, C-reactive protein, carcinoembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Koma et al 35 retrospectively analyzed the data of 332 patients with lung cancer, including 109 women and 223 men who were divided into groups according to RDW values of ≥15% and <15%; the findings of their study confirmed that high levels of RDW are associated with advanced stage disease and indicate poor prognosis in the patients. Similarly, Ichinose et al 22 demonstrated that a high RDW value was significantly associated with increased morbidity and reduced survival in 992 elderly patients who had undergone NSCLC resection.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Koma et al 35 retrospectively analyzed the data of 332 patients with lung cancer, including 109 women and 223 men who were divided into groups according to RDW values of ≥15% and <15%; the findings of their study confirmed that high levels of RDW are associated with advanced stage disease and indicate poor prognosis in the patients. Similarly, Ichinose et al 22 demonstrated that a high RDW value was significantly associated with increased morbidity and reduced survival in 992 elderly patients who had undergone NSCLC resection.…”
Section: Discussionmentioning
confidence: 91%
“…Inflammatory response, RDW, and several widely used plasma inflammatory markers, such as C‐reactive protein level, erythrocyte sedimentation rate, and interleukin‐6 level, are positively correlated with each other, and RDW is considered to be an inflammatory marker in patients with cancer. Additionally, malnutrition, which is associated with a deficiency of various minerals and vitamins, such as iron, folic acid, and vitamin B12, as well as low protein levels, has also been linked to elevated RDW levels in patients with cancer. Finally, oxidative stress is related to red blood cell survival and could be a possible mechanism of action of RDW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that lung cancer patients with increased peripheral blood leukocytes showed increased mortality [ 3 5 ], and the number of lymphocytes and their abnormal functions were also indicators of prognosis [ 4 , 5 ]. HCT is one of the erythrocyte parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that high RDW levels are a negative prognostic indicator for these diseases, and in ammation is the mechanism leading to these high levels [13] . There is increasing evidence that elevated RDW levels are also associated with poor prognosis in a variety of cancers, including hepatocellular carcinoma (HCC) [18][19] , esophageal cancer [20][21] , lung cancer [22] and hematological malignancies [23] . However, a review of the previous related literature shows some research limitations.…”
Section: Introductionmentioning
confidence: 99%